Бежин луг: рассказы / И. С. Тургенев ; [художник И. Горбатый] - Тургенев Иван Сергеевич (Внеклассное чтение, 2023)
Экземпляры: аб. (20230921) / Инвентарный номер: 63844 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 87 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44